The Relationship Between Family Support and Work-Family Balance among Surabaya Health Facility Security Center Employees During the COVID-19 Pandemic - Ero Diah Wahjuningdiah; Indriati Paskarini (The Indonesian Journal of Occupational Safety and Health, 2022)
Introduction: Surabaya Health Facility Security Center employees experienced anxiety during the Covid-19 pandemic. Anxiety is closely related to Work-Family Balance. The balance of roles between work and family is inseparable from family support. This study intended to analyze the relationship between family support and work-family balance. Method: This study used quantitative research with a cross-sectional design. The population consisted of employees at BPFK Surabaya. The sample included 74 pre-selected employees via simple random sampling. The variables in this study were family support (support from family members and family support for work) and Work-Family Balance (family work conflict (FWC), work family conflict (WFC), work family facilitation (WFF), and family work facilitation (FWF)). The data processing was performed using the Smart Partial Least Square test. Result: The study results indicate that there is a high value for family support of 62 (83.8%) and a high value for family support for work at 45 (60,8%). WFC was found to be low at 43 (58.1%), FWC was also low at 43 (58.1%), WFF was given as high at 52 (70.3%), and FWF was high at 54 (73%) respondents. The results indicate that there is a significant positive relationship between family support and WFB (p value = 0.008 <0.05). Family support for work has a significant positive relationship with WFB (p value = 0.027 <0.05). Conclusion: Family support (family support and family support for work) has a relationship with Work-Family Balance.